1997
DOI: 10.1063/1.365101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neutron irradiation on magnetic properties in the low alloy Ni-Mo steel SA508-3

Abstract: A study on the radiation damage and recovery of neutron irradiated vessel steel using magnetic Barkhausen noise J. Appl. Phys. 85, 5726 (1999); 10.1063/1.370265Changes in magnetic parameters of neutron irradiated SA 508 Cl. 3 reactor pressure vessel forging and weld surveillance specimensThe B-H hysteresis loop and Barkhausen noise have been measured in the neutron irradiated SA508 steel of 45 m thickness. The coercive force of B-H loop showed a slow change up to a neutron dose of 10 14 n/cm 2 and increased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In addition, the magnetic method is nondestructive and can be used for direct measurements of pressure vessels besides Charpy specimens. Previous studies showed that magnetic properties of pressure vessel steels change after neutron irradiation [12][13][14][15][16]. However, these studies were mainly focused on fluence dependence of the magnetic properties and the role of Cu and Ni which are important for irradiation embrittlement has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the magnetic method is nondestructive and can be used for direct measurements of pressure vessels besides Charpy specimens. Previous studies showed that magnetic properties of pressure vessel steels change after neutron irradiation [12][13][14][15][16]. However, these studies were mainly focused on fluence dependence of the magnetic properties and the role of Cu and Ni which are important for irradiation embrittlement has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the alloy, magnetic Barkhausen noise is almost always decreased with irradiation (Sipahi et al 1994;Park et al 1997b) due to domain wall pinning, and typically coercivity and permeability are increased, though not always (Park et al 1997a;Park et al 1999b). Irradiation processes that produce point defects and small defect clusters can be effectively probed as a function of dose for small doses using these methods and linear responses are found initially.…”
Section: Irradiated Steels -Barkhausen and Other Magnetic Propertiesmentioning
confidence: 99%
“…In spite of the deep understanding of magnetic properties in these steels, however, results of magnetic properties in neutron irradiated steels are still controversial [4,[19][20][21][22][23][24][25][26]. For instance, in A533B nuclear pressure vessel steels irradiated to the fluence of about 1 Â 10 19 n cm À2 , H c was found to decrease after neutron irradiation [21][22][23], whereas some groups reported the increase or no [19,20].…”
Section: Introductionmentioning
confidence: 99%